Agglomeration Economics 2010
DOI: 10.7208/chicago/9780226297927.003.0002
|View full text |Cite
|
Sign up to set email alerts
|

Estimating Agglomeration Economies with History, Geology, and Worker Effects

Abstract: Does productivity increase with density? We revisit the issue using French wage and TFP data. To deal with the 'endogenous quantity of labour bias (i.e., urban agglomeration is consequence of high local productivity rather than a cause), we take an instrumental variable approach and introduce a new set of geological instruments in addition to standard historical instruments. To deal with the 'endogenous quality of labour bias (i.e., cities attract skilled workers so that the effects of skills and urban agglome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

23
397
1
8

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 329 publications
(429 citation statements)
references
References 45 publications
23
397
1
8
Order By: Relevance
“…The estimates for the density elasticity of output per worker are nonetheless close to the estimates of the density elasticity of tfp in Combes et al (2010). 12…”
Section: Our Main Estimating Equation Issupporting
confidence: 56%
See 2 more Smart Citations
“…The estimates for the density elasticity of output per worker are nonetheless close to the estimates of the density elasticity of tfp in Combes et al (2010). 12…”
Section: Our Main Estimating Equation Issupporting
confidence: 56%
“…shown that these historical instruments yield results similar to alternative instruments based on geology (Combes et al, 2010) and are robust to the inclusion of many local characteristics. Of course, the validity of an instrument is always potentially problematic.…”
Section: Our Main Estimating Equation Ismentioning
confidence: 69%
See 1 more Smart Citation
“…Perhaps most fundamentally, biases may result if either the workers or job opportunities in large and dense urban areas are systematically more or less conducive to job matching. Indeed, recent research indicates that it is important to account for worker characteristics and composition effects in studies of the effects of urban agglomeration (Combes et al, 2008(Combes et al, , 2010Abel, Dey, and Gabe, 2012). As such, we include a wide array of individual-level characteristics, including choice of college major, and account for differences in the economic structure and performance of metropolitan areas in all of our models.…”
Section: Introductionmentioning
confidence: 99%
“…Empirical contributions in this area stress the positive role of urbanization and localization economies in determining worker productivity (Henderson (1986), Henderson (2003) and Combes, Duranton, Gobillon, and Roux (2007)), wages (Wheaton and Lewis (2002)) and economic growth (Glaeser, Kallal, Scheinkman, and Shleifer (1992), Henderson, Kuncoro, and Turner (1995)). Incorporating these agglomeration economies in a tax competition model predicts that agglomeration rents dampen the mobility of firms and capital across borders which allows governments to set higher tax rates.…”
Section: Introductionmentioning
confidence: 99%